Upstream, downstream : exploring watershed connections - Rae, Rowena (Orca footprints., 2021)
Explores the science behind watersheds, and highlights the relationship between watersheds and plants, animals, and humans. Examines the negative effects of humans on watersheds, and profiles activists and scientists who are working to protect watersheds. Includes color photographs, fact boxes, a glossary, and additional resources.